Percutaneous left atrial appendage closure vs warfarin for atrial fibrillation: a randomized clinical trial - Reddy, Vivek Y; Sievert, Horst; Halperin, Jonathan; Doshi, Shephal K; Buchbinder, Maurice; Neuzil, Petr; Huber, Kenneth; Whisenant, Brian; Kar, Saibal; Swarup, Vijay; Gordon, Nicole; Holmes, David; et al. (JAMA, 2014)
IMPORTANCE: While effective in preventing stroke in patients with atrial fibrillation (AF), warfarin is limited by a narrow therapeutic profile, a need for lifelong coagulation monitoring, and multiple drug and diet interactions. OBJECTIVE: To determine whether a local strategy of mechanical left atrial appendage (LAA) closure was noninferior to warfarin. DESIGN, SETTING, AND PARTICIPANTS: PROTECT AF was a multicenter, randomized (2:1), unblinded, Bayesian-designed study conducted at 59 hospitals of 707 patients with nonvalvular AF and at least 1 additional stroke risk factor (CHADS2 score ≥1). Enrollment occurred between February 2005 and June 2008 and included 4-year follow-up through October 2012. Noninferiority required a posterior probability greater than 97.5% and superiority a probability of 95% or greater; the noninferiority margin was a rate ratio of 2.0 comparing event rates between treatment groups. INTERVENTIONS: Left atrial appendage closure with the device (n = 463) or warfarin (n = 244; target international normalized ratio, 2-3). MAIN OUTCOMES AND MEASURES: A composite efficacy end point including stroke, systemic embolism, and cardiovascular/unexplained death, analyzed by intention-to-treat. RESULTS: At a mean (SD) follow-up of 3.8 (1.7) years (2621 patient-years), there were 39 events among 463 patients (8.4%) in the device group for a primary event rate of 2.3 events per 100 patient-years, compared with 34 events among 244 patients (13.9%) for a primary event rate of 3.8 events per 100 patient-years with warfarin (rate ratio, 0.60; 95% credible interval, 0.41-1.05), meeting prespecified criteria for both noninferiority (posterior probability, >99.9%) and superiority (posterior probability, 96.0%). Patients in the device group demonstrated lower rates of both cardiovascular mortality (1.0 events per 100 patient-years for the device group [17/463 patients, 3.7%] vs 2.4 events per 100 patient-years with warfarin [22/244 patients, 9.0%]; hazard ratio [HR], 0.40; 95% CI, 0.21-0.75; P = .005) and all-cause mortality (3.2 events per 100 patient-years for the device group [57/466 patients, 12.3%] vs 4.8 events per 100 patient-years with warfarin [44/244 patients, 18.0%]; HR, 0.66; 95% CI, 0.45-0.98; P = .04). CONCLUSIONS AND RELEVANCE: After 3.8 years of follow-up among patients with nonvalvular AF at elevated risk for stroke, percutaneous LAA closure met criteria for both noninferiority and superiority, compared with warfarin, for preventing the combined outcome of stroke, systemic embolism, and cardiovascular death, as well as superiority for cardiovascular and all-cause mortality. TRIAL REGISTRATION: clinicaltrials.gov Identifier: NCT00129545.
Keywords: kardiovaskulární nemoci; Cardiovascular Diseases; Stroke; Prosthesis Implantation; Atrial Appendage; antikoagulancia; senioři; Aged; Male; Anticoagulants; Atrial Fibrillation; lidé; Treatment Outcome; lidé středního věku; Humans; síňové ouško; Bayesova věta; Middle Aged; implantace protézy; srdeční katetrizace; senioři nad 80 let; fibrilace síní; Aged, 80 and over; Warfarin; rizikové faktory; mužské pohlaví; výsledek terapie; Bayes Theorem; Cardiac Catheterization; analýza přežití; embolie; cévní mozková příhoda; Risk Factors; Embolism; ženské pohlaví; Survival Analysis; Female; warfarin